(untitled) (Fiep Bulletin - online, 2011)
The growing increase of the elderly population and its constant fight for a better quality of life has become the physical activity one of the most important aspects for elderly people in search of a greater autonomy in the practice of activities of daily life (ADL`s), and contributing in the maintenance of the functional capacity. Having in mind these assumptions, the goal of the present study is to identify the main factors that motivate elderly people to practice physical activities in two nucleuses (places) of working of the Program Active Life: Municipal Park and Swimming Lagoon. For the collect of data, two questionnaires were applied, the first one for the characterization of the sample with questions related to the frequent practice of physical activity and a second one that approaches the question of the "Motivation for the Physical activity", formulated in the Laboratory of Psychology of the Sport-LAPE ..,/S-UNIBH in Belo Horizonte MG, where are presented questions about the importance of the reasons for the practice of physical activity, containing 27 questions related in three different dimensions. Participated and were evaluated in the study 48 people from both sexes at the age of 60 to 85 years old, frequent in the Program Active Life in the nucleus Municipal Park and Swimming lagoon. In both nucleuses the results showed that seven factors were more associated and that four factors were less associated to motivation. Therefore, according to the given information, the motivational factors more important for the practice of the physical activity by the ones who were interviewed are, above all the ones related to psychological aspects related to interests, the pleasures and the sensation of humour and the physiological related to the improvement of the physical condition, the health state and the quality of life.